Identification of an I(Na)-dependent and I(to)-mediated proarrhythmic mechanism in cardiomyocytes derived from pluripotent stem cells of a Brugada syndrome patient - Ma, Dongrui (Sci Rep, 2018)
Brugada syndrome (BrS) is an inherited cardiac arrhythmia commonly associated with SCN5A mutations, yet its ionic mechanisms remain unclear due to a lack of cellular models. Here, we used human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from a BrS patient (BrS1) to evaluate the roles of Na(+) currents (I(Na)) and transient outward K(+) currents (I(to)) in BrS induced action potential (AP) changes. To understand the role of these current changes in repolarization we employed dynamic clamp to “electronically express” I(K1) and restore normal resting membrane potentials and allow normal recovery of the inactivating currents, I(Na), I(Ca) and I(to). HiPSC-CMs were generated from BrS1 with a compound SCN5A mutation (p. A226V & p. R1629X) and a healthy sibling control (CON1). Genome edited hiPSC-CMs (BrS2) with a milder p. T1620M mutation and a commercial control (CON2) were also studied. CON1, CON2 and BrS2, had unaltered peak I(Na) amplitudes, and normal APs whereas BrS1, with over 75% loss of I(Na), displayed a loss-of-I(Na) basal AP morphology (at 1.0 Hz) manifested by a reduced maximum upstroke velocity (by ~80%, p < 0.001) and AP amplitude (p < 0.001), and an increased phase-1 repolarization pro-arrhythmic AP morphology (at 0.1 Hz) in ~25% of cells characterized by marked APD shortening (~65% shortening, p < 0.001). Moreover, I(to) densities of BrS1 and CON1 were comparable and increased from 1.0 Hz to 0.1 Hz by ~ 100%. These data indicate that a repolarization deficit could be a mechanism underlying BrS.